2017
DOI: 10.1097/cpm.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Pneumonia With Autoimmune Features: Overview of Proposed Criteria and Recent Cohort Characterization

Abstract: The accurate diagnosis of interstitial lung disease (ILD) is essential for optimal prognostication and management. While connective tissue disease (CTD) is among the most common causes of ILD, some patients have features suggestive of autoimmunity without meeting criteria for a specific CTD. To help define and study this disease entity more uniformly, a 2015 research statement proposed consensus-based criteria and coined the term “interstitial pneumonia with autoimmune features” (IPAF). In this review, we summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…As demonstrated, IPAF studies have shown substantial heterogeneity among patients meeting IPAF criteria with regards to clinical features, disease behaviour and response to treatment. This heterogeneity has been well described in previous reviews [45–49] and confirmed in more recent studies. As such, we suggest that IPAF is unlikely to represent a distinct interstitial lung disease.…”
Section: Discussionsupporting
confidence: 83%
“…As demonstrated, IPAF studies have shown substantial heterogeneity among patients meeting IPAF criteria with regards to clinical features, disease behaviour and response to treatment. This heterogeneity has been well described in previous reviews [45–49] and confirmed in more recent studies. As such, we suggest that IPAF is unlikely to represent a distinct interstitial lung disease.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in recent years a subset of patients has been described, who have idiopathic interstitial pneumonia (IIP) and autoimmune features (IPAF), who do not meet the criteria for a connective tissue disease (CTD) but have at least one sign or symptom suggestive of a CTD and at least one serological test reflective of an autoimmune process [ 21 ]. These patients have been better characterised, and some studies also suggest that patients who met the IPAF criteria had a significantly worse survival than those with IIP without autoimmune features [ 22 ], although substantial variability in outcome has been reported [ 23 ]. As in hypersensitivity pneumonitis, the mechanisms and genetic susceptibility triggering the autoimmune process is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ILDs can be of known cause, e.g., drug related, environmental and/or occupational, and systemic diseases; or of unknown cause, e.g., idiopathic interstitial pneumonia (IIP), granulomatous diseases, and other disorders such as lymphangioleiomyomatosis. Among systemic diseases, connective tissue disease (CTD) is one of the most common causes of ILD [4] .…”
Section: Introductionmentioning
confidence: 99%